Analisis Hukum Perjanjian Kerja Waktu Tertentu Terhadap Pekerja Di Hungrypedia Gorontalo Berdasarkan Undang – Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Rizky Dwitama Bagaskara Modjo; Nirwan Junus; Waode Mustika (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
An employment agreement is also known as an employment relationship between the employer and the worker, when making an agreement between the worker and the employer, and where the worker must fulfill the conditions set by the employer and vice versa the employer must fulfill the rights and obligations of the worker . The purpose of this study is to find out the explanation related to the implementation of work for a certain time and what obstacles occur in the implementation of work agreements for a certain time at Hungrypedia Gorontalo. The type of research conducted in this research is to use normative research methods. The process of implementing a specific time work agreement at Hungrypedia Gorontalo involves explaining the contents of the agreement to workers and workers who have understood and agreed to it. The current obstacle at Hungrypedia Gorontalo is a work schedule problem.